The Health Implications of Meal Skipping Amongst the Elderly and the Strategies for Improvement of Their Healthy Food Consumption in Ugheli, Delta State - Okadigwe John Chukwujekwu (Britain International of Exact Sciences (BIoEx) Journal, 2023)
This study delves into the critical realm of the health implications of meal skipping among the elderly and delineates strategies for the enhancement of healthy food consumption within the unique context of Ugheli, Delta State. As the elderly populace plays an indispensable role in shaping the social, cultural, and familial tapestry of any community, understanding the dietary habits and their impacts on health becomes paramount. The research design comprises both experimental and survey methods, integrating dietary experiments with comprehensive questionnaires. Ugheli, a culturally diverse city in Delta State, Nigeria, forms the geographical scope of this study. The population encompasses 19,235 pensioners, representing a significant segment of the community. Three hundred and sixty-eight respondents, including retirees and health professionals, participated in the study, yielding a response rate of 98%. The findings highlight a pressing concern: a substantial proportion of the elderly in Ugheli grapples with undernutrition, particularly among females. Moreover, meal skipping among the elderly yields a host of adverse health effects, including metabolic disruptions, weight gain, elevated blood pressure, and impaired cognitive function. To mitigate these issues, the study posits evidence-based strategies for bolstering healthy food consumption. These strategies encompass discouraging meal skipping, promoting whole-grain intake, encouraging food fortification, and reducing excessive carbohydrate consumption. Notably, consensus prevails among both male and female respondents and health professionals regarding the significance of these strategies. The implications extend to public health policies and community development in Ugheli, Delta State.